2012
DOI: 10.1002/ccd.24403
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin pretreatment in patients undergoing elective PCI to reduce the incidence of myocardial periprocedural necrosis: The ROMA trial

Abstract: High loading dose of rosuvastatin within 24 hr before elective PCI seems to decrease the incidence of periprocedural myocardial necrosis during a period of 12-months compared to the standard treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 21 publications
1
30
0
2
Order By: Relevance
“…This change may be attributed to a significant reduction of nonfatal myocardial infarctions. The incidence of PMI in our trial was higher than that in the ARMYDAR-ACS [4] or ROMA trials [5]. The different diagnostic criteria of PMI may have led to this result; in the latter trials, PMI was diagnosed by the increase of creatine kinase-MB instead of cTn I.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…This change may be attributed to a significant reduction of nonfatal myocardial infarctions. The incidence of PMI in our trial was higher than that in the ARMYDAR-ACS [4] or ROMA trials [5]. The different diagnostic criteria of PMI may have led to this result; in the latter trials, PMI was diagnosed by the increase of creatine kinase-MB instead of cTn I.…”
Section: Discussionmentioning
confidence: 50%
“…Clinical trials have revealed the efficacy of high-dose statin treatment in significantly reducing the incidence of PMI among patients after coronary revascularization [35]. However, high-dose statin administration has been associated with severe side effects, including increased risk of new-onset diabetes, liver damage, rhabdomyolysis, and intracerebral haemorrhage [68].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the ROSEMARY study [28] suggests that early high-dose rosuvastatin therapy (40 mg before treatment plus maintenance for 7 days) in patients with ST elevation MI undergoing primary PCI did not improve periprocedural myocardial perfusion or reduce infarct volume measured by magnetic resonance imaging compared with the conventional low-dose rosuvastatin regimen. On the contrary, in the ROMA trial, high loading dose of rosuvastatin (40 mg) within 24 h before elective PCI decreased the incidence of periprocedural MI compared to the standard treatment [29]. Furthermore, Takano et al [30] reported that the incidence of periprocedural MI was reduced more effectively by high-dose than by low-dose rosuvastatin in statin-näive patients.…”
Section: Discussionmentioning
confidence: 95%
“…Periprocedural MI is defined as an elevation of troponin (either I or T) values >5 x 99th percentile upper reference limit (URL) in patients with normal baseline values (≤99th percentile URL) or a rise of troponin values >20 % if the baseline values were elevated and are stable or falling [29]. Secondary endpoints are: 1) the combined occurrence of 1-month major adverse cardiovascular events (MACE, including death, MI, stroke or the need for unplanned revascularization) in the 4 treatment arms.…”
Section: Study Endpointsmentioning
confidence: 99%
“…Many data support the pleiotropic effect of statins showing a rapid anti-inflammatory and antioxidant effects with consequently a myocardial protection by reperfusion damage (13,14). The concentration of C-reactive protein after statin therapy, decrease in some studies (15)(16)(17).…”
mentioning
confidence: 94%